Genetic Divergence Among a Breeding Population of Hancornia Speciosa Gomes (Mangabeira) as Determined by Multivariate Statistical Methods - Maia, Maria Clideana Cabral; Araújo, Mirian Fernandes Carvalho; Borges de Araújo, Lucio; Dias, Carlos Tadeu dos Santos; Cláudio de Oliveira, Luís; Cruz, Cosme Damião; Vasconcelos, Lúcio Flavio Lopes; Macedo, Luciano Medina; Yokomizo, Gilberto Ken Iti; Costa Lima, Paulo Sarmanho da (European Scientific Journal, ESJ, 2018)
The mangabeira its figure out among the mains native fruit tree explored by extractivism in Brasil. The objective evaluate the genetic divergence of landraces in orientation of crosses using multivariate techinics. The complete random blocks experimental design with four repetitions was used to evaluate twelve quantitative characteristics from twelve genotypes elite of mangabeiras concerning to divergence genetic using the software R (2012). Three groups genetically divergent were composed by biplot graphic and stored by UPGMA cluster analysis (Unweighted Pair-Group Method using Arithmetic Average / Weighted Clustering Method not using the Arithmetic Mean) showing genetic diversity and variability among 12 mangabeira accesses. Forty-four possible crosses are planned among genotypes of genetically dissimilar three groups and six among individuals in group III. Multivariate techniques were appropriate in the study of genetic divergence.